2020
DOI: 10.1007/s10803-020-04563-8
|View full text |Cite
|
Sign up to set email alerts
|

A High Prevalence of Autism Spectrum Disorder in Preschool Children in an Immigrant, Multiethnic Population in Sweden: Challenges for Health Care

Abstract: This study examines the prevalence of autism spectrum disorder (ASD) in preschool children in an immigrant population. Possible risk factors for ASD and individual needs for the children and their families are described, as well as implications for health care. The estimated minimum prevalence for ASD in the area was 3.66% for children aged 2–5 years. Multiple risk factors and extensive individual needs for the children and their families were observed. The high prevalence of ASD and the plethora of needs in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Expat mothers in the UAE with children with ASD shared their experiences about initial diagnoses, family members, school and therapy, and the wider community. While the average age of diagnosis in the present study matches the global average of 5 years (van't Hof et al, 2020), it is delayed diagnosis in comparison to several developed countries (Linnsand et al, 2021). Several mothers felt that diagnosis and treatment were often delayed as symptoms of ASD were confused with other comorbid impairments such as delayed language development.…”
Section: Discussionsupporting
confidence: 46%
“…Expat mothers in the UAE with children with ASD shared their experiences about initial diagnoses, family members, school and therapy, and the wider community. While the average age of diagnosis in the present study matches the global average of 5 years (van't Hof et al, 2020), it is delayed diagnosis in comparison to several developed countries (Linnsand et al, 2021). Several mothers felt that diagnosis and treatment were often delayed as symptoms of ASD were confused with other comorbid impairments such as delayed language development.…”
Section: Discussionsupporting
confidence: 46%
“…Data were collected from an ongoing prospective longitudinal study of young children diagnosed with ASD in an area with a high prevalence of people with multiethnic background and/or socioeconomically disadvantaged situation in Gothenburg, Sweden. Details regarding the multidisciplinary team for both assessments and interventions have been described previously ( 55 , 56 ). Two of the authors (GN, pediatrician and child psychiatrist and PL, psychologist) had personally examined all included children, met them and their families in interventions over a period of at least two years and re-examined all children in the multiprofessional team at follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the parents had non-Swedish background (93%). For more details regarding participants, see Linnsand et al ( 56 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was remarkable that a significantly high rate of children from Eastern European families were found in the most severe group of ASD, especially in the southern population. It has been suggested that environmental factors related to migration, such as stressful experiences or suboptimal pregnancy and birth conditions, may be associated with an increased risk of ASD, particularly in cases of comorbid ID or severe ASD (Crafa & Warfa, 2015;Kawa et al, 2017;Linnsand et al, 2021). We could also be facing an under-diagnosis of milder cases due to a lack of awareness of cultural differences in the screening and diagnosis.…”
Section: Asd and Associated Sociodemographic Factorsmentioning
confidence: 99%